2008
DOI: 10.1152/ajpcell.00342.2008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of overexpression of metallothionein-1 on cell cycle progression and zinc toxicity

Abstract: Metallothioneins (MTs) have an important role in zinc homeostasis and may counteract the impact of oversupply. Both intracellular zinc and MT expression have been implicated in proliferation control and resistance to cellular stress, although the interdependency is unclear. The study addresses the consequences of a steady-state overexpression of MT-1 for intracellular zinc levels, cell cycle progression, and protection from zinc toxicity using a panel of cell lines with differential expression of MT-1. The pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Zinquin ethyl ester, instead of zinquin, was chosen because of an ethyl ester in place of the 6-methoxy group of toluenesulfonamidoquinoline in the molecular structure of zinquin ethyl ester, which facilitates its retention in living cells and enhances its fluorescence. Using zinquin ethyl ester, we were able the identify the subcellular localization of free labile Zn(II) in the extranu- clear secretory granule, which is consistent with the findings of two previous reports (33,37). Results from both methods indicate that free labile zinc increases along with the extracellular zinc concentration, whereas resveratrol tends to increase the free labile zinc level in ZA and ZS cells but to decrease the free labile zinc level in ZN and ZD cells (not statistically significant; Figs.…”
Section: Discussionsupporting
confidence: 90%
“…Zinquin ethyl ester, instead of zinquin, was chosen because of an ethyl ester in place of the 6-methoxy group of toluenesulfonamidoquinoline in the molecular structure of zinquin ethyl ester, which facilitates its retention in living cells and enhances its fluorescence. Using zinquin ethyl ester, we were able the identify the subcellular localization of free labile Zn(II) in the extranu- clear secretory granule, which is consistent with the findings of two previous reports (33,37). Results from both methods indicate that free labile zinc increases along with the extracellular zinc concentration, whereas resveratrol tends to increase the free labile zinc level in ZA and ZS cells but to decrease the free labile zinc level in ZN and ZD cells (not statistically significant; Figs.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have shown that zinc induces MT synthesis and subsequently plays a role in antioxidation. MT binds to heavy metal ions and expels them from the cytoplasm, thereby protecting cells from oxidative damage .…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the 2nd shell amino acids surrounding the catalytic zinc ion of these enzymes indicated that the active site of TACE is more polar than that of MMP‐2 and of other MMPs (Solomon ). The consequences of a steady‐state overexpression of metallothioneins (MT‐1) for intracellular zinc levels, cell cycle progression, and protection from zinc toxicity was addressed using a panel of cell lines with differential expression of MT‐1, suggesting that zinc availability is normally not limiting for cell cycle progression (Smith ).…”
Section: Zinc In Cell Injury and Inflammationmentioning
confidence: 99%